Advances in Pathogenesis of Sjögren's Syndrome. (7th October 2021) - Tian, Yao; Yang, Hongyi; Liu, Na; Li, Yan; Chen, Jie
Abstract : Sjögren's syndrome (SS) is a chronic autoimmune disease of unknown etiology that mainly involves exocrine glands. Patients present with dry mouth and eyes, fever, arthralgia, and other systemic symptoms. In severe cases, the quality of life of patients is affected. At present, there is no cure for SS, and the treatment options are extremely limited. In recent years, studies of patients and animal models have identified abnormalities of immune cell function and cytokines to be involved in SS. A systematic review of the literature may clarify the etiology and pathogenesis of SS, as well as provide a theoretical basis for the development of new drugs for the treatment of SS.